Rapid Formation and Flexible Expression of Memories of Subliminal Word Pairs - Reber, Thomas P.; Henke, Katharina (Frontiers in Psychology, 2011)
Our daily experiences are incidentally and rapidly encoded as episodic memories. Episodic memories consist of numerous associations (e.g., who gave what to whom where and when) that can be expressed flexibly in new situations. Key features of episodic memory are speed of encoding, its associative nature, and its representational flexibility. Another defining feature of human episodic memory has been consciousness of encoding/retrieval. Here, we show that humans can rapidly form associations between subliminal words and minutes later retrieve these associations even if retrieval words were conceptually related to, but different from encoding words. Because encoding words were presented subliminally, associative encoding and retrieval were unconscious. Unconscious association formation and retrieval were dependent on a preceding understanding of task principles. We conclude that key computations underlying episodic memory – rapid encoding and flexible expression of associations - can operate outside consciousness.